Respuesta :
Answer:
24
Step-by-step explanation:
Since this is a right triangle, we can use the Pythagorean theorem
a^2+b^2 = c^2 where a and b are the legs and c is the hypotenuse
7^2 + b^2 = 25^2
49 + b^2 = 625
Subtract 49 from each side
49+b^2 -49 = 625-49
b^2 = 576
Take the square root of each side
sqrt(b^2) = sqrt(576)
b = 24
Step-by-step explanation:
[tex]hypotenuse {}^{2} \: = base {}^{2} + \: perpendicular {}^{2} \: \\ \\ base {}^{2} = 25 {}^{2} - 7 {}^{2} \\ \\ base {}^{2} = 625 - 49 \\ \\ base {}^{2} = 576 \\ \\ base = \sqrt{576} \\ \\ base = 24 \\ \\ [/tex]